Critical bending radius of thin single-crystalline silicon with dome and pyramid surface texturing. (November 2017) - Woo, Jeong-Hyun; Kim, Young-Cheon; Kim, Si-Hoon; Jang, Jae-il; Han, Heung Nam; Choi, Kyoung Jin; Kim, Inho; Kim, Ju-Young
Abstract: Four-point bending tests are performed on 50-μm-thick single-crystalline silicon (Si) wafers with dome- and pyramid-shaped surface patterns, which are used as flexible Si solar cells. Surface patterns, which act as stress concentrators, reduce the flexural strengths, leading to larger critical bending radius. The critical bending radii of surface-textured Si are much smaller than the calculated values for a single-notch geometry. The finite element analysis shows that the stress concentrations at the tips of the surface patterns effectively disperse in fine and periodic dome and irregular pyramid patterns. Graphical abstract: